2014
DOI: 10.1093/mnras/stu1667
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino-heated winds from rotating protomagnetars

Abstract: We calculate the steady-state properties of neutrino-driven winds from strongly magnetized, rotating proto-neutron stars ('proto-magnetars') under the assumption that the outflow geometry is set by the force-free magnetic field of an aligned dipole. Our goal is to assess proto-magnetars as sites of r-process nucleosynthesis and gamma-ray burst engines. One dimensional solutions calculated along flux tubes corresponding to different polar field lines are stitched together to determine the global properties of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 83 publications
1
43
0
Order By: Relevance
“…Other estimates of r-process material production yield ≈ 0.01M ⊙ for a SN magnetized driven jet (Nishimura et al 2015) and 0.01M ⊙ for a magnetized neutrino-driven wind (Vlasov et al 2014). Since these processes require rapid rotation, and hence low metallicity, these authors estimate that the rate of such events is low compared to regular SNe.…”
Section: +76mentioning
confidence: 96%
See 1 more Smart Citation
“…Other estimates of r-process material production yield ≈ 0.01M ⊙ for a SN magnetized driven jet (Nishimura et al 2015) and 0.01M ⊙ for a magnetized neutrino-driven wind (Vlasov et al 2014). Since these processes require rapid rotation, and hence low metallicity, these authors estimate that the rate of such events is low compared to regular SNe.…”
Section: +76mentioning
confidence: 96%
“…However, the low rate can be consistent with a peculiar astrophysical explosion associated with a core collapse of massive stars. For instance, a magnetically powered outflow from newly born magnetars has been proposed as the site of the r-process nucleosynthesis (Suzuki & Nagataki 2005;Metzger et al 2008;Winteler et al 2012;Vlasov et al 2014;Nishimura et al 2015;Mösta et al 2015). This could happen in a peculiar SN (e.g.…”
Section: Peculiar Core-collapse Supernovaementioning
confidence: 99%
“…If the PNS has a strong magnetic field and rotates rapidly, the magnetic force is important for the dynamics of the wind and for the thermal history of the fluid element (Metzger et al 2007;Vlasov et al 2014). In Metzger et al (2007), the criterion for which the wind is magnetically driven is shown (see their discussion above Equation (17) in their paper).…”
Section: The Effect Of the Rotation And The Magnetic Field Of The Pnsmentioning
confidence: 99%
“…Even if baryon loading were to cease abruptly, a minimum time would be required to clear the jet of baryons, which we estimate to be t d ∼ 0.01 s as the dynamical timescale near the base of the wind (Ref. [36], Fig. 9).…”
mentioning
confidence: 92%